An experimental and numerical anvestigation of slamming loads on ship forms - Korkmaz, Fatih Cüneyd (My University, 2016)
This study is performed to investigate the slamming impact experimentally and numerically. Slamming phenomenon has an impulse character and produces high magnitude local pressure pulses that are very short in duration, followed by a lower magnitude residual pressure lasting tens of milliseconds. Various types of geometrical shapes are used when carrying slamming tests in order to obtain impact characteristics. The experiments are conducted with three different groups of specimens; namely, advancing deadrise angle ones; cylinder and sphere, constant deadrise angle ones; wedge and cones, and ship models; bulbous bow and catamaran. Drop tests have been set up for studying the impact forces, dropping test objects from various heights toward water surface. The slamming coefficient is calculated via experimental results and then compared with analytical and numerical results. The current analytical approaches for slamming impact are mainly calculation of the added mass, so the visualization of the experiments are significant. Therefore, free fall tests are recorded via a high speed camera to observe the water deformation, rise of the water and water jet propagates along the surface of the immersing body. The effect of the deadrise angle is demonstrated via constant deadrise angle shapes by measuring the total slamming impact. The faster the velocity and the lower the deadrise angle it has, the higher the impact force it encounters. These parameters along with the total drop mass and the total volume (buoyancy force) are the main factors shaping the rise of the water and splash characteristics. Along with the experimental investigation, numerical approaches are performed using a commercial code, ANSYS-Fluent, based on finite volume method for a 2-d rigid cylinder. The results are compared with the current experimental results via non-dimensional slamming impact coefficient. Secondly, the effect of hydrophobicity is investigated experimentally in water entry of all test shapes in this study. Hydrophobicity is the way of increasing the contact angle of a fluid on a solid surface. In this study, hydrophobic surface is created by applying a coating on the test objects. The water deformation phenomena like jet formation, water pileup, and splashing and flow separation on solid surfaces are compared under the hydrophobic effects. It is observed that flow separation occurs earlier with hydrophobic surfaces causing no pressure pulse occurrence on the solid surface at larger penetration depths. The pictures are also captured for hydrophobic coated cases from a high speed camera. It is indicated that hydrophobicity also causes larger pileups with faster jet flows indicating more kinetic energy transference to the fluid. The non-dimensional pileup coefficient is introduced to compare the rate of transferring energy. Along with the high speed images, the impact loads are calculated and compared with when hydrophobicity is present by employing strain gauge measurements. It is found that the peak values during slamming are smaller with hydrophobic surfaces promoting a reduction in the impact forces while distributing the pressure pulses on a larger wetted area. The effect of flexibility is also studied by using different rigidity of cylinders in case of the advanced deadrise angle shapes. The relatively rigid and flexible materials are tested and less slamming impact is measured for the relatively flexible cylinder. The water exit of cylinder and sphere is also investigated experimentally. Different fluid dynamics phenomena like free surface evolution, deformation and break up of free surface, the amount of drag water thickness and horizontal width, and water detachment from the solid surfaces during a water exit event have been examined. The deformation of the cylinder and sphere surface due to water exit is measured for different releasing depths. Finally the wedge and cylinder shape models are tested with macro scale roughness surface to show the possible application of ship surface to gain similar effect with hydrophobic coated surface. The early water separation from the surface is also observed at wedge and cylinder with ridged surfaces.

Bu çalışmada gemilerdeki dövünme yükleri deneysel ve numerik olarak incelenmiştir. Dövünme, dalgalı denizlerde gemi gövdesinin serbest su yüzeyinden ayrılıp tekrar suya girişi esnasında olan, milisaniye mertebelerinde ve geminin yüksek oranda basınca maruz kalındığında olan fenomendir. Dövünme testinde, çarpma etkilerini ölçmek için farklı geometrik şekiller kullanılmıştır. Deneysel çalışmada kullanılan şekillerin yüzeyleri ile serbest su yüzeyi arasındaki değişikliklerine göre, giriş açısının her bir aşamadaki derinlik değerinde farklılık gösteren silindir ve küreyi değişken açılı, buna karşı her derinlik değerinde aynı açı değeri gösteren kama, koni sabit açılı ve gemi modelleri, katamaran ve gemi baş kısım modeli olarak sınıflandırılmıştır. Serbest düşme deneyleri, araştırılan geometrinin belirli yükseklikten suya girişi sağlayarak üzerine gelen çarpma kuvvetlerini ölçmek için kurulmuştur. Boyutsuz bir değer olan dövünme katsayısı; deney, analitik ve numerik yöntemlerle elde edilerek karşılaştırılmıştır. Dövünme kuvvetinin tespitinde kullanılan analitik yöntemlerde ek su kütlesi kullanılır ve yapılan deneylerde cisimlerin suya giriş aşamalarının görselliği önemlidir. Bu sebepten düşürme testlerinde cisimlerin suya girişi hızlı kamerayla kayıt altına alınarak suyun deformasyonu, suyun yükselmesi ve yüzey üzerinde jet akışının dağılması görselleştirilmiştir. Kama ve koni gibi sabit açılı suya girişleri olan geometrik şekillerde giriş açısının etkisi farklı açılı modeller kullanılarak gösterilmiştir. Yüksek hızlı girişte ve düşük açılı girişlerde en fazla çarpma kuvvetleriyle karşılaşılırken giriş açısı büyüdüğünde daha az çarpma kuvvetlerine maruz kalındığı görülmüştür. Bu parametreler ile düşürülen cismin ağırlığı ve toplam hacmi (kaldırma kuvveti) yükselen suyun ve sıçrayan suyun şekillenmesinde ki sebeplerdir. Deneysel çalışmanın akabinde numerik çalışma, Ansys Fluent programı ile 2 2 boyutlu silindirin suya girişi, sonlu hacim metoduyla gerçekleştirilmiştir. Nümerik sonuçlar ile deney, boyutsuz katsayı olan dövünme katsayısı değeriyle karşılaştırılmıştır. Deneysel olarak incelenen bütün şekiller, hidrofobik kaplandığı haliyle de düşürme testleri gerçekleştirilmiştir. Hidrofobik kaplama sıvının yüzey ile yaptığı kontak açısı değerini arttırır, yani suyun yüzeyle temas alanını azaltır. Jet akışın şekillenmesi, suyun yapı ile temas noktalarını, suyun dağılması ve ayrılması gibi suyun deformasyonu olayları kaplama yapılan ve yüzeyde işlem yapılmadığı haliyle düşürülen testlerle karşılaştırılmıştır. Kullanılan şekiller hidrofobik kaplı olarak suya girdiğinde cisim üzerindeki etkileşim halinde olan suyun erken ayrılması, daha büyük ötelenen su kütlesi, daha hızlı su akışına dolayısıyla daha büyük oranlarda bir enerji transferi meydana geldiği hidrofobik kaplı testlerde gözlemlenmiştir. Oluşturulan boyutsuz bir katsayı değeri olan pileup değeri tanıtılmış ve hızlı kamera görüntüleriyle ölçülen değerler karşılaştırılmıştır. Sonuçta, cisimler hidrofobik kaplandığında daha az dövünme kuvvetlerine ulaşılırken, tepe değerle ulaşması için daha fazla ıslak alana ulaşması gerektiği bulunmuştur. Farklı sertlik değerine sahip malzemelerle üretilen silindirler kullanılarak dövünmedeki elastisitenin etkisi araştırılmıştır. Göreceli olarak rijid ve esnek olan silindirler kullanılarak, esnek silindirde daha az dövünme kuvvetleri ölçülmüştür. Sudan çıkış problemi, silindir ve küre için deneysel olarak çalışılmıştır. Serbest su yüzeyinin değişimi, deformasyonu, ayrılması, serbest su yüzeyinden çıktıktan sonraki suyun yatay ve dikey kalınlıkları ve cismin ötelediği su miktarı sudan çıkış çalışmalarında incelenmiştir. Bu farklılıklar cisimlerin farklı derinliklerden çıkışları için ayrı ayrı araştırılmıştır. Silindir ve kürenin sudan çıkışlarındaki oluşan deformasyonlar, farklı derinliklerden bu cisimlerin serbest bırakılmasıyla ölçülmüştür. Son olarak büyük ölçekli yüzey pürüzlülüğüne sahip ve muhtemel hidrofobik yüzey özelliklerini kazanabilecek ve gemilerde pratik uygulama sağlayabilecek kama ile silindir şekilli cisimler test edilmiştir. Suyun yüzeyden erken ayrılması pürüzlü kama ve silindirde de aynı şekilde gözlemlenmiştir.
Tez (Doktora) - Yıldız Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2016
Keywords: Water entry; Slamming; Impact force; Hydrophobicity; Gemilerde dövünme; Çarpma kuvveti; Hidrofobiklik